A refined method for computing bibliographic coupling strengths. Issue 2 (May 2019) - Shen, Si; Zhu, Danhao; Rousseau, Ronald; Su, Xinning; Wang, Dongbo
Highlights: A new formula for calculating bibliographic coupling strength is provided. It is based on the TF-IDF formula as used in information retrieval. A derived formula for similarity calculation between documents is provided. The feasibility of these new formulae is shown on a large dataset. Abstract: We propose a new method for computing the bibliographic coupling strength between two documents. This new method is based on the TF-IDF formula from the field of information retrieval. It is shown that this formula is a valid alternative for the original formula introduced by Kessler and is, from a probabilistic point of view, a correction of the Vladutz-Cook formula. We further define a cosine based similarity formula generalizing the Sen-Gan coupling angle formula.